How Degas Distinguished Himself From The Other Impressionists - Perspective (NC, 2023)
Despite his long and fruitful association with the impressionists, Edgar Degas preferred to be called a realist. His focus on urban ...
Droits : Source YouTube a verifier
Keywords: artiste peintre; peintures; artistes peintres; Peintres; Musées